Exploring the Green Energy: Factors Influencing Battery Electric Vehicles Adoption in Madhya Pradesh Region - Asati, Parul; Raghuwanshi, Sandeep; Vashisht, Anil; Muley, Deepa; Khare, Vikas Kumar (International Review of Management and Marketing, 2024)
Electric vehicles (EVs) are quickly becoming a viable alternative to vehicles powered by fossil fuels such as gasoline, diesel, and compressed natural gas (CNG), which has prompted customers to think about these vehicles as a means to alleviate the increasing environmental problems brought about by fuel depletion and greenhouse gas (GHG) emissions. The point of this article is to explore potential elements that effect consumers’ intentions to adopt electric vehicles. To accomplish this, the author conducted in-depth interviews with a wide range of stakeholders, including suppliers, academics and consultants, BEV owners, prospective consumers, and government officials. A study is carried out in Madhya Pradesh with the aim of determining the elements that influence the decision to purchase electric automobiles. An innovation diffusion theory–based questionnaire was developed to elucidate both the consumer’s perspective and the factors impacting the widespread adoption of electric vehicles. Before purchasing an electric vehicle, consumers should weigh the advantages and disadvantages listed via multiple response analysis. The study’s findings will shed light on customer preferences, which in turn will assist policymakers in India in developing policies that encourage the purchase and usage of electric vehicles.